Swedish Multinationals and Competition from High- and Low-Wage Locations - Henrik Braconier; Karolina Ekholm (The Research Institute of Industrial Economics (IUI), 1999)
This study uses data on Swedish multinationals to estimate cross elasticities of labour demand in different locations. With a vertical decomposition of the firm's activities, whether there is substitution or complementarity between employment in different parts of the firm will depend on whether wage changes lead to a relocation of activities or simply to changes in marginal costs and/or demand for inputs in other parts of the firms. We find that there is some evidence of a substitutionary relationship between employment in the Swedish parts of the firms and employment in other high-income locations, but we do not find any evidence of substitution stemming from employment in low-income locations. We find mainly a relationshipof complementarity between employment in different affiliates.
Keywords: F23; J23; 330; Labour demand; Multinational firms; Vertically integrated firms; Räumlicher Wettbewerb; Arbeitsnachfrage; Vertikale Integration; Multinationales Unternehmen; Schweden